Foreign language learning, today and tomorrow : essays in honor of Emma M. Birkmaier - Birkmaier, Emma Marie, 1908-1985; Arendt, Jermaine D.; Lange, Dale L.; Myers, Pamela J. (Pergamon Press, 1979)
Foreign Language Learning, Today and Tomorrow is a collection of papers that attempts to shed lights into the concerns and issues that will be encountered by foreign language instructors.